Navigating trans visibilities, trauma and trust in a new cervical screening clinic. Issue 10 (2nd August 2022) - Gibson, Alexandra F.; Drysdale, Kerryn; Botfield, Jessica; Mooney-Somers, Julie; Cook, Ted; Newman, Christy E.
Abstract: Trans and gender diverse people are globally recognised as being under-served in clinical services, with significant implications for their health. During a national reorientation of the Australian cervical screening programme – from Papanicolaou smears to human papillomavirus screening – we conducted interviews with 12 key informants in cancer policy, sexual and reproductive health and trans health advocacy to understand how trans people's needs and experiences were being accounted for and addressed in health policy and practice. Themes captured the complexities of increasing visibility for trans people, including men and non-binary people with a cervix. These complexities reflect the extensive system and cultural change required in asking policymakers and practitioners to think differently about who is at risk of a disease typically associated with cisgender women. Informants drew on the language of trauma to explain the resistance many trans people feel when engaging with clinical services, particularly relating to sexual and reproductive health. In doing so, they argued for increasing resources and processes to elicit trans people's willingness to put their trust in such services. Thinking critically about the relationship between the politics of trans visibilities, trauma and trust can support effective and inclusive approaches to transgender health.